Differences in Behavior After Dental Health Counseling with Zoom Meetings for Middle School Students - Sukini Sukini; Ni Kade Rinawati; Irmanita Wiradona (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
RISKESDAS data shows that the number of dental health problems is about 55.6% in junior high school students in Bali Province in 2018. The reason is because of low oral health behaviour, therefore dental health counseling is expected to overcome these problems. The aim of this study was to know the differences of behavior after being given oral health counseling to junior high school students.This type of research is quasi experimental with a one-to-one design pre-test and post-test groups. The sample consisted of 60 junior high school students with a purposive sampling technique. Data analysis with Wilcoxon test.The results of statistical tests in the study showed that there were significant differences related to knowledge (p = 0.000) 0.05, attitudes (p = 0.000) 0.05, and actions (p = 0.000) 0.05, after being given counseling with zoom meeting. Most of the students during pretest had moderate knowledge, attitudes, and actions, after being given counseling with a zoom meeting, the posttest scores increased to good.Keyword : Counseling; behaviour; zoom meeting